PENENTUAN UKURAN LOT GABUNGAN DENGAN BARGAINING GAME DAN CONSIGNMENT UNTUK PEMANUFAKTUR DAN PEMBELI TUNGGAL - Jalesviva Joy; Docki Saraswati; Rahmi Maulidya (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2013)
This paper considers the integrated inventory model, where the ordering lot is no longerdetermined by the buyer, but it is determined by both parties in order to minimize the totalinventory cost. There are three approaches in determining the joint lot size: Joint Economic LotSize (JELS), Joint Economic Lot Size with Bargaining Game, and Joint Economic Lot Size withConsignment. On JELS with Bargaining Games, the manufacturer will offer rebates to thebuyer, since buyer will be at the disadvantage side if the manufacturer only offers JELS.Furthermore, on model JELS with Consignment, the manufacturer will own the product until itis used by the buyer. Using JELS, manufacturer makes a savings of 8.73% while the buyersuffered a loss of 3.37%. The result of using the JELS with Bargaining Game will give themanufacturer a savings of 6.63%, while the inventory cost for the buyer is the same with theinitial condition (individually). This paper concludes that using the JELS with consignment willprovide savings to the manufacturer as well as for the whole system.